Leukoencephalopathy with calcifications and cysts: Genetic and phenotypic spectrum. Issue 1 (7th October 2020) - Crow, Yanick J; Marshall, Heather; Rice, Gillian I; Seabra, Luis; Jenkinson, Emma M; Baranano, Kristin; Battini, Roberta; Berger, Andrea; Blair, Edward; Blauwblomme, Thomas; Bolduc, Francois; Boddaert, Natalie; et al.
Abstract: Biallelic mutations in SNORD118, encoding the small nucleolar RNA U8, cause leukoencephalopathy with calcifications and cysts (LCC). Given the difficulty in interpreting the functional consequences of variants in nonprotein encoding genes, and the high allelic polymorphism across SNORD118 in controls, we set out to provide a description of the molecular pathology and clinical spectrum observed in a cohort of patients with LCC. We identified 64 affected individuals from 56 families. Age at presentation varied from 3 weeks to 67 years, with disease onset after age 40 years in eight patients. Ten patients had died. We recorded 44 distinct, likely pathogenic, variants in SNORD118 . Fifty two of 56 probands were compound heterozygotes, with parental consanguinity reported in only three families. Forty nine of 56 probands were either heterozygous (46) or homozygous (three) for a mutation involving one of seven nucleotides that facilitate a novel intramolecular interaction between the 5′ end and 3′ extension of precursor‐U8. There was no obvious genotype–phenotype correlation to explain the marked variability in age at onset. Complementing recently published functional analyses in a zebrafish model, these data suggest that LCC most often occurs due to combinatorial severe and milder mutations, with the latter mostly affecting 3′ end processing of precursor‐U8.